Advanced and emerging agricultural innovations for securing food, climate and ecosystems in Moroccan oasis - Rachid Mrabet (Journal of Oasis Agriculture and Sustainable Development, 2022)
In Morocco, oasis ecosystems cover 15% of country’s lands and are bright spots of rich biodiversity and multi-functionality but hot spots of land degradation, social vulnerability and water and food insecurity. Hence there is a need to shift from assessing risks and hazards in these ecosystems to effectively capture key drivers and pursue solutions and measures to reduce vulnerability and enhance adaptive and productive capacity. In other terms, the food-environment dilemma requires urgently revitalizing these fragile agro-ecosystems in order to re-nurture the population, to strengthen society growth and food-related value chains and bring back resilience and sustainable development. In doing so, it is imperative to enforce, develop and encourage adoption of state of the art but adapted innovations and support knowledge sharing processes and approaches that drive implementation and up/deep scaling of innovations within ecosystems and by communities. A large array of innovations and technologies is emerging pertaining to advanced biotechnology, agro-ecology, smart-irrigation management, disease monitoring, control and safety, food industry, livestock, soil security, landscape management and institutional policy and governance. The paper seeks to present an integrated view of these stock takes and how they can help in addressing simultaneously climate change and food security, spatial prioritization, closing gaps, strong interfacing of society and ecology and achieving land degradation neutrality.